กลยุทธ์ในการเพิ่มแรงจูงใจในการปฏิบัติงานของข้าราชการครูและบุคลากร ทางการศึกษาในศตวรรษที่ 21 - ช่วงโชติ, พิชชฎาภัทร์; ไชยจันดี, พิมพ์ใจ; ขนฺติธมฺโม (ศิลากุล), พระมหานพรัตน์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 1 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 1 : มกราคม - เมษายน 2567, 2024)
The personnel development is a crucial process for the long-term growth and success of an organization. It should start with assessing and analyzing the needs of both the organization and its employees. This approach allows for the design of training and development programs that align with these needs, such as specialized skill training, management skill enhancement, and lifelong learning support. As a result, employees will acquire up-to-date knowledge and skills, which can be effectively utilized in their work. Another key strategy for personnel development is creating an environment that fosters learning and innovation. Organizations should encourage employees to share knowledge and experiences through teamwork, knowledge exchange activities, and support for attending relevant seminars and conferences. Cultivating an organizational culture that values openness and learning will inspire employees and motivate them to continually develop themselves. Finally, personnel development should emphasize continuous mentoring and coaching. Managers and supervisors should take on the role of advisors and coaches for their employees. Effective mentoring and coaching help employees set clear development goals and plans. This also builds trust and engagement between employees and management, resulting in higher commitment and dedication to their work. Ultimately, this approach contributes to building a strong and highly capable team in the long term.